Contribution of agriculture to climate change and low-emission agricultural development in Asia and the Pacific - Jeetendra Prakash Aryal (Asian Development Bank Institute (ADBI), 2022)
The agriculture sector in Asia and the Pacific region contributes massively to climate change, as the region has the largest share of greenhouse gas (GHG) emissions from agriculture. The region is the largest producer of rice, a major source of methane emissions. Further, to achieve food security for the increasing population, there has been a massive increase in the use of synthetic fertilizer and energy in agricultural production in the region over the last few decades. This has led to an enormous rise in nitrous oxide (N2O; mostly from fertilizer-N use) and carbon dioxide (mostly from energy use for irrigation) emissions from agriculture. Besides this, a substantial increase in livestock production for meat and dairy products has increased methane emissions, along with other environmental problems. In this context, this study conducts a systematic review of strategies that can reduce emissions from the agriculture sector using a multidimensional approach, looking at supply-side, demand-side, and cross-cutting measures. The review found that though there are huge potentials to reduce GHG emissions from agriculture, significant challenges exist in monitoring and verification of GHG emissions from supply-side measures, shifting to sustainable consumption behavior with regard to food consumption and use, and the design and implementation of regulatory and incentive mechanisms. On the supply side, policies should focus on the upscaling of climate-smart agriculture primarily through expanding knowledge and improving input use efficiency in agriculture, while on the demand side, there is a need to launch a drive to reduce food loss and waste and also to move towards sustainable consumption. Therefore, appropriate integration of policies at multiple levels, as well as application of multiple measures simultaneously, can increase mitigation potential as desired by the Paris Agreement and also help to achieve several of the United Nations' SDGs.
Keywords: Q15; Q18; Q24; Q54; 330; agriculture; climate change; low-emission agriculture; Asia and the Pacific